Latvia - The Quest for Jobs and Growth : A World Bank Country Economic Memorandum, Volume 1. Policy Briefing - World Bank (Washington, DC, 2013)
As a strong reformer among the Central and Eastern European Countries (CEEC), Latvia has recorded a dramatic economic improvement recent years, with relatively strong growth, increased investment rates, and clear signs of easing labor market conditions. A stabilization package designed around a fixed exchange rate regime, and prudent fiscal policies, as well as structural reforms, have yielded good results, although the current account deficit is still high, and the fiscal stance has deteriorated somewhat since 2001. Unemployment has declined from its peak of almost 21 percent in the mid-1990s, to about 12 percent in 2002. Since 2000, youth and the elderly have been more active in the labor market, while prime age employment is on the rise. Factors explaining the decline in unemployment include: changes in demographics; stronger growth and investment; and, progress in structural reforms. Yet, some substantial problems remain and must be addressed. Migration and commuting between regions are impaired by high transportation costs and underdeveloped housing markets; incomes are low in rural areas nationwide; Latvia's labor force features a skills mismatch; taxes on labor use are relatively high, which includes high contributions to social programs; and, investors have raised concerns on factors that would prevent the development of knowledge-intensive sectors. Convergence to European Union (EU) income levels will take time - Latvia's per capita income stands only at about 33 percent of the EU average in purchasing power standards. The 2000 European Council of Lisbon set ambitious targets for raising employment rates in the EU, though in the short to medium term, implementation of the remaining policy agenda, could help Latvia meet the Lisbon targets. Furthermore, as Latvia becomes a member of the EU in May 2004, and prepares to adopt the euro, its flexible labor market will be key for sustaining macroeconomic performance, and accelerating convergence. The report proposes pursuing sound macroeconomic policies to further job creation; reducing informality: a lower tax burden on labor use is likely to have a fiscal cost in the short term, but this must be weighed against the potentially great positive effects of attracting business to the formal sector; thus, pursuing structural reforms to continue attracting foreign direct investment; improving skills for low-wage, unskilled workers through training programs, and the acceleration of reforms in the education sector. Finally, within the social sectors recommendations suggest changing the composition of social protection spending to improve social assistance benefits for poor families, while improving the rates of receipt of transfer payments across social groups.